2007
DOI: 10.1007/s00540-007-0550-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of droperidol decreases postoperative nausea and vomiting after gynecological laparoscopy

Abstract: We evaluated whether or not routine prophylaxis with 2.5 mg of droperidol would efficiently prevent postoperative nausea and vomiting (PONV). Fifty-two patients scheduled for elective gynecological laparoscopic surgery were eligible for this study. Anesthesia was induced using propofol, fentanyl, and vecuronium, and maintained with sevoflurane in nitrous oxide, fentanyl, and vecuronium. Patients were randomized to one of two groups: group 1 patients (n = 23) received 2.5 mg droperidol intravenously when the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Williams et al [25] applied patient-controlled analgesia with morphine in patients who had abdominal hysterectomies and in the treatment of postoperative pain; they reported that droperidol was effective in preventing PONV. Gan et al [14] found droperidol and patient-controlled analgesia effective in preventing PONV after orthopedic surgery; these results were similar to those found after gynecologic operations [26,27]. Droperidol which affects the QT interval has been reported to cause cardiac complications [28,29].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Williams et al [25] applied patient-controlled analgesia with morphine in patients who had abdominal hysterectomies and in the treatment of postoperative pain; they reported that droperidol was effective in preventing PONV. Gan et al [14] found droperidol and patient-controlled analgesia effective in preventing PONV after orthopedic surgery; these results were similar to those found after gynecologic operations [26,27]. Droperidol which affects the QT interval has been reported to cause cardiac complications [28,29].…”
Section: Discussionsupporting
confidence: 66%
“…Williams et al [25] found droperidol to be effective in preventing PONV, but its sedation effect was more apparent. Mitsunari et al [26] found no side effects from droperidol. Bolton et al [35] detected sedation in 1 of 84 cases with droperidol, and Kovac [32] reported sedation in 7% of 580 cases in a multicenter study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discussion the authors stated that Mitsunari et al [5] found ondansetron to be superior to metoclopramide and droperidol. How should these investigators come to this result when they only investigated droperidol in the prevention of PONV?…”
mentioning
confidence: 99%